Relational communication and illusionary loyalty: Moderating role of self-construal - Hossain, Mehdi T; Chonko, Lawrence B (Industrial Marketing Management, 2018)
In this research we demonstrate how various facets of communication influence customer loyalty in a B2B selling environment. Palmatier, Scheer, and Steenkamp (2007) show that salesperson owned loyalty (customers' loyalty specific to the salesperson) can be differentiated from customers' overall loyalty to the firm. We demonstrate how various facets of communication differentially influence salesperson owned loyalty and loyalty to the firm. We find that greater bidirectional flow of communication enhances both salesperson owned loyalty and customers' loyalty to firm. However, greater frequency of communication enhances only salesperson owned loyalty. Formality in communication negatively influences salesperson owned loyalty and positively influence customers' loyalty to firm. In addition, we find an interesting moderation effect of these relationships by customers' self-construal. Theoretical and practical implications of our findings are discussed.
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/023-861-182-258-749 tex.type: [object Object]
Keywords: Communication facets; Loyalty to firm; Relationship marketing; Salesperson owned loyalty; Self construal; dept.mkt; peer-reviewed